ANALISIS TINGKAT LITERASI HUKUM EKONOMI SYARIAH DI KALANGAN MAHASISWA: IMPLIKASI TERHADAP PRAKTIK KEUANGAN SYARIAH - Kurnia Fitri Rahma Dani; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The level of sharia economic law literacy has a crucial role in influencing the implementation of the sharia financial system among students. A deep understanding of sharia economic principles, such as transparency, fairness and the prohibition of usury, encourages students to be more active in utilizing sharia-based financial services. However, the low level of literacy in this field is one of the challenges in developing the Islamic finance industry, especially among students as potential future leaders. This research aims to examine students' level of understanding of sharia economic law and its impact on sharia financial practices. The research results reveal that lack of access to practice-based education, limited information, and minimal use of digital technology are the main factors hindering increasing literacy in sharia economic law. Therefore, a comprehensive strategy is needed to increase student understanding, such as strengthening practice-based curricula, holding seminars and workshops, optimizing digital media, as well as the active role of the academic community with support from the government and the Islamic finance industry. With a systematic and sustainable strategy, increasing sharia economic legal literacy is expected to strengthen the sharia financial industry and encourage a more inclusive and just economic system.